2015
DOI: 10.1016/j.devcel.2015.04.019
|View full text |Cite
|
Sign up to set email alerts
|

Zygotic Genome Activation Triggers Chromosome Damage and Checkpoint Signaling in C. elegans Primordial Germ Cells

Abstract: Recent findings have identified highly transcribed genes as a source of genome instability; however, the degree to which large-scale shifts in transcriptional activity cause DNA damage was not known. One example of a large-scale shift in transcriptional activity occurs during development, when maternal regulators are destroyed and zygotic genome activation (ZGA) occurs. Here, we show that ZGA triggers widespread chromosome damage in the primordial germ cells of the nematode C. elegans. We show that ZGA-induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
63
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(65 citation statements)
references
References 50 publications
2
63
0
Order By: Relevance
“…1). 5 Interestingly, we also noticed that Z2 and Z3 did not divide synchronously, rather either Z2 or Z3 would divide first, and the other would follow after another 2 or so hours. The basis for this asynchrony in cell cycle reentry is not known.…”
Section: Checkpoint Control Of Z2/z3 Cell Cycle Reentrymentioning
confidence: 99%
See 3 more Smart Citations
“…1). 5 Interestingly, we also noticed that Z2 and Z3 did not divide synchronously, rather either Z2 or Z3 would divide first, and the other would follow after another 2 or so hours. The basis for this asynchrony in cell cycle reentry is not known.…”
Section: Checkpoint Control Of Z2/z3 Cell Cycle Reentrymentioning
confidence: 99%
“…We opted to pursue the basis for the sterility phenotype, and observed that chk-1(RNAi) adults showed a complete absence of a germline. 5 When we looked earlier in development, we saw that unfed chk-1 (RNAi) L1s had a superficially normal primordial gonad, where Z2/Z3 were arrested at G2/prophase, as inferred by a measured 4N DNA content. 5 This implied that the chk-1(RNAi) sterility phenotype was manifested sometime between the L1 stage and adulthood.…”
Section: Checkpoint Control Of Z2/z3 Cell Cycle Reentrymentioning
confidence: 99%
See 2 more Smart Citations
“…These events are associated with a spike in transcription-coupled DNA damage that needs to be repaired for proper division to ensue. 23 In light of these studies, it is intriguing to speculate that xnd-1 or nos-1/2 may alter DNA damage repair in the L1 larvae leading to PGC loss and/or reduced proliferation. In support of this hypothesis, xnd-1 mutants are hypersensitive to gamma irradiation and the brood size defects of xnd-1 are partially suppressed by mutations in the checkpoint kinase, atm-1 (McClendon and Yanowitz, submitted).…”
Section: Cell Cycle Regulation Of Pgcsmentioning
confidence: 99%